Economic Discrimination Against Black Characters in The Help: A Gramscian Hegemonic Approach - Renata, Dhea Amelia; Sumaryani, Sri (JELITA, 2026)
The Help by Kathryn Stockett critically examines the lives of Black domestic workers in 1960s Jackson, Mississippi, highlighting persistent economic inequalities. Utilizing Antonio Gramsci’s theory of hegemony, this research employs a qualitative textual analysis approach to examine the novel’s dialogues and narratives, revealing two key forms of economic discrimination faced by Black characters: inequalities in the work and wage system, and barriers to social mobility. These forms of oppression intersect to sustain racial hierarchy and structural inequality. The study concludes that the novel not only portrays historical racial discrimination in the South but also illustrates how hegemonic power normalizes economic subordination through cultural consent, thus highlighting the relevance of the discussion on social justice.